Adenoid Cystic Carcinoma of the Lacrimal Gland: High Dose Adjuvant Proton Therapy to Improve Patients Outcomes - Lesueur, Paul; Rapeaud, Etienne; De Marzi, Ludovic; Goudjil, Farid; Levy, Christine; Galatoire, Olivier; Jacomet, Pierre Vincent; Dendale, Rémi; Calugaru, Valentin (Frontiers in Oncology, 2020)
Introduction: Lacrymal cystic adenoid carcinoma is a rare disease for which optimal treatment is still debated. In fact, despite aggressive treatment such as eye sparing surgery or orbital exenteration, following by adjuvant radiotherapy, local recurrence and distant metastatic disease are common. This study aims to describe outcomes of eye surgery associated with high dose exclusive adjuvant proton beam irradiation. Materials&Methods: This is a monocentric institutional retrospective study. We retrospectively reviewed records of patients treated in our institution since 2008 with high dose adjuvant proton irradiation for a lacrymal cystic adenoid carcinoma up to a maximum of 75.6Gy(RBE). Other histologies or patients treated with a mix of photon-proton were excluded. A total of 15 patients were finally included. Results: Fifteen patients (80% women, 100% Performance status 0-1) with locally advanced disease (33% T3-T4, 47% R1-R2) were included. After a median follow-up of 67.4 months [13.4-122] the 3 years Overall Survival, local Progression free survival, and progression free survival rates were 78%, 70% and 58% respectively. Six patients exhibited a local recurrence. All patients with conservative surgery maintained their base-line visual acuity and visual field at last follow up. Four patients developed brain radionecrosis. Conclusion: This is the largest series of patients with ACC treated with high dose adjuvant proton therapy. Proton therapy is a safe and efficient treatment and should be considered as an adjuvant irradiation modality to privilege, for patients with lacrimal ACC after conservative or radical eyeball surgery. Dose delivered to temporal lobe should be limited to avoid brain radionecrosis.